National Evaluation of the National Institute of Justice Grants to Combat Violent Crimes Against Women on Campus Program, 2000-2002 - DuPree, Cheron ([Verlag nicht ermittelbar], 2003)
This study was undertaken as a process evaluation of the Grants to Combat Violence Against Women on Campus Program (Campus Program), which was conducted by the Institute for Law and Justice under a grant from the National Institute of Justice (NIJ) and funding from the Violence Against Women Office (VAWO). The Campus Program was comprised of 38 colleges or universities, which received funding in 1999 and 2000. Part 1 data consist of basic demographic information about each campus and the violence against women programs and services available at each site. Data for Part 2, collected from questionnaires administered to grant project staff, documented perceptions about the Campus Program project and participation and collaboration from those involved in the partnership with each college or university (i.e., non-profit, non-governmental victim service providers).